Yield of Fungal Surveillance Cultures in Pediatric Hematopoietic Stem Cell Transplant Patients: A Retrospective Analysis and Survey of Current Practice. (5th November 2013) - Youngster, Ilan; Sharma, Tanvi S.; Duncan, Christine N.; McAdam, Alexander J.
Abstract : In the United States, fungal surveillance cultures are commonly performed in pediatric hematopoietic stem cell transplant recipients. These cultures have limited clinical utility for predicting systemic fungal disease. Stool cultures show the highest yield for identifying fungal colonization. Abstract: Background. Fungal surveillance cultures (FSCs) have been proposed as predictors for development of invasive fungal disease (IFD) and identifiers of the causative organism, although data supporting these are limited and predate universal initiation of antifungal prophylaxis. We aimed to define the epidemiology of fungal colonization and investigate the utility of FSCs for predicting IFD in recipients of pediatric hematopoietic stem cell transplantation (HSCT). Methods. FSCs performed from 2007 to 2011 on HSCT patients and laboratory and clinical data were reviewed, and incidence of IFD was determined. Descriptive analyses of culture results were performed to determine the yield of FSCs and their utility. A Web-based survey of national pediatric HSCT providers was undertaken to evaluate current practice and the relevance of our results. Results. Five thousand six hundred eighteen FSCs from nares, throat, and stool from 360 patients were processed. Of these, 14.8% were positive: 30.3% from stool, 13.2% from throat, and 0.9% from nares; 64.4% of patients had > 1 positive FSCs. Thirty (8.3%) patients had IFD. IFD occurred in 7.9% and 10.1% of patients with positive and negative FSCs, respectively ( P = .25). Antifungal coverage was changed in 69 patients (29.9%) after positive FSC; 8.6% developed IFD (n = 2 of 6 pathogen concordance with FSC) compared with 6.7% ( P = .59) who had no treatment change (n = 3 of 11 concordance). The response rate to the survey was 70.8%; 40% of institutions reported performing routine FSC. Twenty-five percent of providers would not change management based on FSC results; overall rating of usefulness of FSCs was low. Conclusions. Although FSCs are commonly performed for pediatric HSCT patients, they have limited utility for predicting IFD.